2015
DOI: 10.1097/md.0000000000001827
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Pap Smear and Diagnosis of High-Grade Vaginal Intraepithelial Neoplasia

Abstract: The aim of this study was to analyze the correlation between the first diagnosis of high-grade Vaginal Intraepithelial Neoplasia (HG-VaIN: VaIN 2–VaIN 3) and the cytological abnormalities on the referral pap smear.All the women with histological diagnosis of HG-VaIN consecutively referred to the Gynecological Oncology Unit of the Aviano National Cancer Institute (Aviano, Italy) from January 1991 to April 2014 and with a pap smear performed in the 3 months before the diagnosis were considered, and an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 29 publications
1
27
0
4
Order By: Relevance
“…In 44.8% of the cases, however, the diagnosis of HG-VAIN was preceded by lesser cytological abnormalities. [ 11 ] These data are interesting, especially when comparing to the correlation between the CIN and the corresponding previous abnormality of cytology test. It was found that a high-grade cervical dysplasia is often preceded by major cytological abnormalities in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 44.8% of the cases, however, the diagnosis of HG-VAIN was preceded by lesser cytological abnormalities. [ 11 ] These data are interesting, especially when comparing to the correlation between the CIN and the corresponding previous abnormality of cytology test. It was found that a high-grade cervical dysplasia is often preceded by major cytological abnormalities in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported [ 11 ] that if cytology test is abnormal, it should be followed by a subsequent colposcopy with more accurate examination of the entire lower genital tract. An accurate examination of the whole vaginal walls and vault must be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the risk factors for VaIN are similar to those for CIN and include sexual activity, smoking, and HPV infection, little is known about VaIN as compared with other neoplasias such as CIN or VIN 7 . Several studies have investigated the prevalence of HPV infection in VaIN; however, among studies reviewed in a 2019 meta‐analysis, only one had a sample size over 300, and most focused on women who underwent hysterectomy 3,6,8‐12 . Furthermore, studies have reported conflicting findings for the rate of HPV infection among women with VaIN.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Colposcopy and further vulvar tissue biopsy should be done if having suspicion, especially for long-term HPV infections even without vaginal dysplasia. [12] However, there is no literature mentioned that whether the vulvar tissue should be also focused, and if it is necessary for biopsy of vulvar tissue in the case of negative cytology? The current manner of cancer surveillance might be just the limitation of this case, by which long-term HPV infection has been neglected and eventually developed into a cause of vulvar tumors.…”
Section: Discussionmentioning
confidence: 99%